2011
DOI: 10.1177/1756283x11402118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of colonic adenomas in patients with nonalcoholic fatty liver disease

Abstract: There was no difference in the prevalence of colonic adenomas when comparing the NAFLD group who had undergone colonoscopy with a group of control patients without NAFLD who had undergone colonoscopy. However, patients with negative ultrasounds appeared to have a lower polyp burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Moreover, a large population based study from Korea comparing the relationship between ultrasound diagnosed NAFLD and colorectal adenomas found a direct association with NAFLD and colonic adenomas [16]. Other studies from USA found similar association between biopsy-confirmed NAFLD and the prevalence of colonic adenomas [17]. Currently, patients with more than 3 colonic adenomas or any adenoma >10 mm are subject to colonoscopic screening every 3 years [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large population based study from Korea comparing the relationship between ultrasound diagnosed NAFLD and colorectal adenomas found a direct association with NAFLD and colonic adenomas [16]. Other studies from USA found similar association between biopsy-confirmed NAFLD and the prevalence of colonic adenomas [17]. Currently, patients with more than 3 colonic adenomas or any adenoma >10 mm are subject to colonoscopic screening every 3 years [18].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD was also associated with multiple colorectal adenomas (≥3) and a tendency towards proximal lesions (right-sided colonic adenomas). Whether the risk of colorectal adenoma increases with NASH compared with simple steatosis is unclear with two relatively small cross-sectional studies demonstrating conflicting results 144 145. Recently, a large cross-sectional study of 26 540 asymptomatic individuals from South Korea however, found the risk for any colorectal neoplasia and advanced colorectal neoplasia to be particularly increased in patients with NAFLD with high NFS or other non-invasive fibrosis scores 146…”
Section: Epidemiological Data Linking Nafld To Risk Of Colorectal Adementioning
confidence: 99%
“…Colorectal cancer (CRC) remains as one of the commonest cancers worldwide, with a million new cases diagnosed each year [1]. In the UK, there are 35,000 new cases of colorectal cancer diagnosed each year [2].…”
Section: Introductionmentioning
confidence: 99%